Occurrence of dermatophytoses in patients from the Sistema Único de Saúde - Sanguino,Talita Carla (2019)
Abstract: Background: Dermatophytosis is a cutaneous disease caused by filamentous keratinophilic fungi belonging to the genera Trichophyton, Microsporum and Epidermophyton, which present a high prevalence in the general population, being among the most common mycoses affecting about 20% of the world's population. Objective: To carry out the epidemiological survey of cases of dermatophytosis in patients from the Sistema Único de Saúde in a regional Laboratory in the period of 5 years (2009 to 2013). Methods: A retrospective study (January 2009 to December 2013) was carried out with a qualitative and quantitative design, through the registry book of the laboratory, Mycology Sector, where cases of patients with suspected dermatomycosis were analyzed. Results: In a 5-year period, a total of 4467 cases were suspected of having a fungal infection. Of these, 68.74% (3071) cases were of dermatomycosis. In relation to cultures with fungal growth, 12.54% (385 cases) were dermatophyte fungi and 7.97% (245 cases) non-dermatophyte fungi were isolated. Among the species identified, there was a higher prevalence of T. rubrum complex (75%), T. mentagrophytes complex (11.68%) and M. canis (7.01%). Regarding the sites analyzed, nail involvement was the most frequent in 75% of the cases. Study Limitations: This work is representative in the studied region. Conclusions: Dermatomycosis samples are the most frequent among all samples of fungal infections from these patients, with the nail being the most affected area and the fungi T. rubrum complex and T. mentagrophytes complex the most frequent.